PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN (STUDI PADA PT. POS INDONESIA (PERSERO)) - Thea Geneveva Josephine Jesajas; Arweni (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2022)
The research objective to find out about (a) how the transformational leadership style at PT.Pos Indonesia (Persero) in Cilaki-Bandung, (b) how the performance of employees at PT. Pos Indonesia (Persero) in Cilaki-Bandung, (c) how much the influence of transformational leadership style on employee performance at PT.Pos Indonesia (Persero) in Cilaki-Bandung. This research used the quantitative and descriptive analysis method. The object of this research is PT. Pos Indonesia (Persero) in Cilaki-Bandung. The data source was a questionnaire by given to 98 respondents. Validity and reliability tests used in this study. The analysis used in this research is descriptive analysis, classic assumption test, simple linear regression. The results show the respondents to the transformational leadership style into good category to 80.71%, the respondents to the performance into very good category to 83.88%. The influence of transformational leadership style on employee performance amounted to 33.2% of the test results on the coefficient determination and t test showed that transformational leadership significantly influence employee performance.